How safe is it to shop? Estimating the amount of space needed to safely social distance in various retail environments. (December 2020) - Ntounis, Nikos; Mumford, Christine; Loroño-Leturiondo, Maria; Parker, Cathy; Still, Keith
Highlights: We explore the problem of capacity for social distancing across various retail environments. We provide guidance to managers as lockdown eases and establishments are allowed to reopen. The paper identifies the minimum amount of space needed per person in different scenarios. We estimate the optimal capacity for retailers to provide a safe environment for shoppers. Abstract: COVID-19 has had a devastating effect on towns and cities throughout the world. However, with the gradual easing of lockdown policies in most countries, the majority of non-essential retail businesses are trying their best to bounce back both economically and socially. Nevertheless, the efforts of retail traders are hampered by uncertainty regarding what capacity measures need to be taken, and there is an urgent need to understand how social distancing can be safely followed and implemented in these spaces. This paper draws from retail space allocation, crowd science, operational research and ergonomics/biomechanics to develop a method for identifying the minimum amount of space an individual needs to socially distance in shops, markets, shopping centres and open commercial spaces, when there are other people present. The area required per person is calculated for both static space (where people are seated, standing or queuing, for example) and dynamic space (where people need to walk freely). We propose our method as a step forward in understanding the very practical problem of capacity, which can hopefully allow retail spaces to operate safely, and minimise the risk of virus transmission.